The axiological image of contemporary teachers - Wiśniewska, Ewa (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The area of considerations undertaken in this study was determined by the value category. The article is a theoretical-research one and its aim is to attempt to characterize the values of modern teachers. This goal was achieved through a statistical presentation of the values indicated by respondents that are valuable to them in life, based on criteria such as: gender, age, type of school, length of work and the degree of professional promotion. On this basis, an attempt was made to define the axiological image of a contemporary teacher.